2023
DOI: 10.3390/land12030619
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Associations between the Built Environment and Cycling Behaviour around Urban Greenways from a Human-Scale Perspective

Abstract: The incorporation of cycling as a mode of transport has been shown to have a positive impact on reducing traffic congestion, improving mental health outcomes, and contributing to the development of sustainable cities. The proliferation of bike-sharing systems, characterised by their wide availability and high usage rates, has made cycling in urban areas more accessible and convenient for individuals. While the existence of a relationship between cycling behaviour and the built environment has been established,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 140 publications
(217 reference statements)
0
4
0
Order By: Relevance
“…The findings revealed a positive correlation between street tree density and both walking distance ( 34 ) and walking duration ( 39 ). Notably, eye-level greenness, as indicated by the GVI, exhibited a significant relationship with extended walking durations within various buffer zones, including 400 m ( 13 , 36 ), 500 m ( 41 ), 800 m ( 13 , 15 , 36 , 40 ), and 1,600 m ( 47 ), for both utilitarian and leisure walking ( 45 ), particularly during weekends ( 49 ). Moreover, the cumulative GVI demonstrated a significantly positive correlation with active travel distance ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings revealed a positive correlation between street tree density and both walking distance ( 34 ) and walking duration ( 39 ). Notably, eye-level greenness, as indicated by the GVI, exhibited a significant relationship with extended walking durations within various buffer zones, including 400 m ( 13 , 36 ), 500 m ( 41 ), 800 m ( 13 , 15 , 36 , 40 ), and 1,600 m ( 47 ), for both utilitarian and leisure walking ( 45 ), particularly during weekends ( 49 ). Moreover, the cumulative GVI demonstrated a significantly positive correlation with active travel distance ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies have delved into the impact of street greenness on cycling frequency or greenway utilization frequency ( 16 , 17 , 47 ). Among these investigations, eye-level greenness emerged as a key factor, demonstrating a remarkable effect on cycling behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is worth noting that certain studies have reported no significant rise in PA among participants residing near greenways (12,34). This phenomenon can be attributed to a range of factors, including external influences such as social trends and psychological variables, as well as internal factors like the accessibility and openness of the greenways (34,42). It is imperative to conduct further research to substantiate the existing findings, which should encompass comprehensive explanations of potential external and internal factors that may have a significant impact on the applicability of these findings to diverse urban areas.…”
Section: Main Findings Of the Meta-analysismentioning
confidence: 99%